Efficient prosthodontic treatment in a young patient with long-standing bulimia nervosa: a clinical report - Kappel, Stefanie; Kreuter, Alexander; Rammelsberg, Peter (The journal of prosthetic dentistry, 2011)
Time-saving, efficient dental treatment is essential for patients in poor dental condition. This clinical report describes a systematic technique for restoration of the visibly-destroyed dentition of a long-term bulimia nervosa patient, including occlusal vertical dimension increase, with composite resin core foundations and prosthetic rehabilitation with ceramic crowns, in only a few treatment sessions. The efficiency of this procedure is gained from composite resin core restorations that establish the new occlusal vertical dimension (OVD) and replace and form the foundation for the subsequent crown preparation.
Gesehen am 28.10.2022